ANALISIS PENYAKIT KARDIOVASKULAR MENGGUNAKAN METODE KORELASI PEARSON, SPEARMAN DAN KENDALL - Windarto, Yudi Eko (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2020)
Cardiovascular disease is a disease that is affected by the heart and blood vessels. There are several main risk factors that cause cardiovascular disease. Risk factors for cardiovascular disease include: high blood pressure, high cholesterol, diabetes, being overweight or obese, age, sex, smoking, and alcohol. The more risk factors you have, the greater the chance of causing cardiovascular disease. In this research, it was developed using the Spearman, Pearson and Kendall correlation methods to analyze data on cardiovascular disease patients. The results showed there was correlation between blood pressure (ap_hi and ap_lo), age, and cholesterol had a strong relationship with cardiovascular disease. Glucose and cholesterol levels also have a strong relationship between one another.